# Find-the-value-of-n-so-that-a-n-1-b-n-1-a-n-b-n-may-become-the-H-M-between-a-and-b-

Question Number 3615 by Rasheed Soomro last updated on 16/Dec/15
$${Find}\:{the}\:{value}\:{of}\:{n}\:{so}\:{that} \\$$$$\frac{{a}^{{n}+\mathrm{1}} +{b}^{{n}+\mathrm{1}} }{{a}^{{n}} +{b}^{{n}} } \\$$$${may}\:{become}\:{the}\:{H}.{M}.\:{between} \\$$$${a}\:\:\:{and}\:\:\:\:{b}. \\$$
Commented by prakash jain last updated on 16/Dec/15
$${n}=−\mathrm{1} \\$$$$\frac{\mathrm{1}+\mathrm{1}}{\frac{\mathrm{1}}{{a}}+\frac{\mathrm{1}}{{b}}}\:=\:\frac{\mathrm{2}{ab}}{{a}+{b}} \\$$
Answered by Yozzii last updated on 16/Dec/15
$${H}.{M},\:{h}=\frac{\mathrm{1}}{\frac{\mathrm{1}}{\mathrm{2}}\left(\frac{\mathrm{1}}{{a}}+\frac{\mathrm{1}}{{b}}\right)}=\frac{\mathrm{2}{ab}}{{a}+{b}}.\:\:\left({a},{b}>\mathrm{0}\right) \\$$$${If}\:{h}=\frac{{a}^{{n}+\mathrm{1}} +{b}^{{n}+\mathrm{1}} }{{a}^{{n}} +{b}^{{n}} } \\$$$$\Rightarrow\:\frac{{a}^{{n}+\mathrm{1}} +{b}^{{n}+\mathrm{1}} }{{a}^{{n}} +{b}^{{n}} }=\frac{\mathrm{2}{ab}}{{a}+{b}} \\$$$$\Rightarrow\left({a}+{b}\right)\left({a}^{{n}+\mathrm{1}} +{b}^{{n}+\mathrm{1}} \right)=\mathrm{2}{ab}\left({a}^{{n}} +{b}^{{n}} \right) \\$$$${a}^{{n}+\mathrm{2}} +{abb}^{{n}} +{aba}^{{n}} +{b}^{{n}+\mathrm{2}} =\mathrm{2}{aba}^{{n}} +\mathrm{2}{abb}^{{n}} \\$$$${a}^{{n}+\mathrm{2}} +{b}^{{n}+\mathrm{2}} ={aba}^{{n}} +{abb}^{{n}} \\$$$${a}^{{n}+\mathrm{2}} −{ba}^{{n}+\mathrm{1}} −{ab}^{{n}+\mathrm{1}} +{b}^{{n}+\mathrm{2}} =\mathrm{0} \\$$$${a}^{{n}+\mathrm{1}} \left({a}−{b}\right)−{b}^{{n}+\mathrm{1}} \left({a}−{b}\right)=\mathrm{0} \\$$$$\left({a}^{{n}+\mathrm{1}} −{b}^{{n}+\mathrm{1}} \right)\left({a}−{b}\right)=\mathrm{0} \\$$$$\Rightarrow{a}={b}\:{or}\:{a}^{{n}+\mathrm{1}} ={b}^{{n}+\mathrm{1}} \:\left(\ast\right). \\$$$${If}\:{a}\neq{b},\:\left(\ast\right)\:{is}\:{true}\:{iff}\:{n}=−\mathrm{1}. \\$$$$\\$$$$\\$$$$\\$$
Commented by Rasheed Soomro last updated on 17/Dec/15
$${For}\:{b}\neq\mathrm{0} \\$$$$\:{a}^{{n}+\mathrm{1}} ={b}^{{n}+\mathrm{1}} \Rightarrow\frac{{a}^{{n}+\mathrm{1}} }{{b}^{{n}+\mathrm{1}} }=\mathrm{1}\:\Rightarrow\left(\:\frac{{a}}{{b}}\right)^{{n}+\mathrm{1}} =\left(\frac{{a}}{{b}}\right)^{\mathrm{0}} \\$$$$\Rightarrow{n}+\mathrm{1}=\mathrm{0}\Rightarrow{n}=−\mathrm{1} \\$$